Pro-Human Rights Leadership on Human Rights-Based Digitalization: Moderating Role of Organizational Culture in University - Sri Wartulas; Surahmadi Surahmadi; Agung Prayogi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research aims to examine the effect of pro-human rights leadership on human rights-based digitalization with organizational culture as a moderating variable in universities. This study uses a quantitative approach with an explanatory design. Data were collected from lecturers and students at Universitas Peradaban using purposive sampling. A total of 455 respondents participated in this research. Data analysis employed Structural Equation Modeling (SEM) to examine the direct and moderating relationships among variables. The findings indicate that pro-human rights leadership positively and significantly affects human rights-based digitalization. Leaders who prioritize fairness, inclusiveness, transparency, and human rights protection are more capable of encouraging ethical and human-centered digital transformation in universities. Furthermore, organizational culture significantly strengthens the relationship between pro-human rights leadership and human rights-based digitalization. Universities with organizational cultures that support human rights values and digital ethics tend to enhance the effectiveness of leadership in implementing inclusive and responsible digital systems. The novelty of this research lies in integrating human rights perspectives into digital transformation studies in higher education and introducing organizational culture as a moderating factor in the relationship between pro-human rights leadership and human rights-based digitalization.